De la banca al sofá La diversificación de los patrones de consumo en San José (1857-1861) - Vega Jiménez, Patricia (Revista de historia., 1991)
The author analyses how and to what extent consumption patterns in San José became more diversified as income expanded for inhabitants of the Central Valley, thanks to production and sale of coffee after 1850.